2018
DOI: 10.1016/j.physb.2017.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface morphology on the optical and electrical properties of Schottky diodes of CBD deposited ZnO nanostructures

Abstract: We report on effect of surface morphology on the optical and electrical properties of chemical bath deposited Zinc oxide (ZnO) nanostructures. ZnO nanostructures were deposited on the seeded conducting indium doped tin oxide substrate positioned in three different directions in the growth solution. Field emission scanning electron microscopy was used to evaluate the morphological properties of the synthesized nanostructures and revealed that the positioning of the substrate in the growth solution affects the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Hari et al prepared open and closed hexagonal ZnO-NRs on ITO by chemical bath deposition (CBD) using equimolar amounts of Zn (NO3)2•6H2O and hexamethylenetetramine for varying deposition times [21]. They found that the NRs grown when the temperature of the bath was set at 95 °C for 4 h had mainly open ends while the ratio of the area of open NRs to closed NRs decreased as chemical bath time was increased from values exceeding 9 h. Mwankemwa et al.showed that the orientation of seed the layer in a growth solution during CBD of ZnO determines the morphology and optical properties and vertically aligned nanorods are grown when the seed layer is facing downwards [22]. Kumar et al studied the difference in the performance of MAPbI3 solar cells using ZnO-NRs on FTO, and flexible ITO coated polyethylene terephthalate (PET) substrates [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hari et al prepared open and closed hexagonal ZnO-NRs on ITO by chemical bath deposition (CBD) using equimolar amounts of Zn (NO3)2•6H2O and hexamethylenetetramine for varying deposition times [21]. They found that the NRs grown when the temperature of the bath was set at 95 °C for 4 h had mainly open ends while the ratio of the area of open NRs to closed NRs decreased as chemical bath time was increased from values exceeding 9 h. Mwankemwa et al.showed that the orientation of seed the layer in a growth solution during CBD of ZnO determines the morphology and optical properties and vertically aligned nanorods are grown when the seed layer is facing downwards [22]. Kumar et al studied the difference in the performance of MAPbI3 solar cells using ZnO-NRs on FTO, and flexible ITO coated polyethylene terephthalate (PET) substrates [23].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are also compatible to produce heterojunctions and could open a new path in the manufacture of optoelectronic devices for different applications [18][19][20]. Usually, heterojunctions are not synthesized using methods in aqueous solutions; such methods involve a great difficulty in optimization, which has led to little use despite their low cost and the good quality of the films that they generate [21][22][23][24]. Weng et al [18] developed a CdS/PbSe heterojunction for high-temperature mid-infrared photovoltaic detector applications.…”
Section: Introductionmentioning
confidence: 99%
“…21 Otherwise, the morphology of a material including size and shape also has an important effect on its properties and applications. 22 It has been reported that ZnFe 2 O 4 with various morphologies could be synthesized by many methods such as mechanochemical method, co-precipitation method, polymer pyrolysis method, sol-gel auto-combustion method, template method, electrospinning method, hydrothermal method and spray drying method. 23,24 Different morphologies can endow ZnFe 2 O 4 with different particle dimensions and surface areas, which could have significant influence on its photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%